Հանրային կապերի և գովազդի դերը ժամանակակից գրադարանի ձևավորման գործում - Մակարյան, Անուշ Սերյոժայի (Հայկական գրադարանային ասոցիացիա)
The activity of modern libraries cannot be imagined without PR and advertising. Especially in the case of a large flow of information, libraries must be able to become competitive in order to deliver it all to the reader more quickly and efficiently. On the international platforms, today also in Armenia, there are many tricks that allow to turn libraries into active and attractive places of entertainment. Of course, this process does not happen quickly in Armenia, especially due to the limited financial resources of libraries, but a trend of development is already visible. In Arme-nia, we consider the reform and preservation of the building conditions, spaces, potential reader and the library to be a priority in Armenia. This requires daily and painstaking work, which must definitely be carried out by specialized teams, so that the goal is justified and the work is effective. Libraries should have specially developed programs with a clear purpose and sequence of actions, which will ensure the result. It is necessary to establish contact with educational institutions, va-rious institutions, organizations, organize meetings, etc. Purpose: to provide information about the library and the services it offers.
Keywords: Ժամանակակից գրադարաններ